Digital Start-Ups in the Global South : Embeddedness, Digitality and Peripherality in Latin America /: Embeddedness, Digitality and Peripherality in Latin America. (2017) - Quinones, Gerardo; Heeks, Richard, 1960-; Nicholson, Brian, 1967-
No abstract available